Pengaruh Human Capital dan Talent Management Terhadap Peningkatan Kinerja Karyawan Pada PT. Telkom Witel Medan - Sianturi, Elhot Nicolas Roganda; Ridho, Hatta; Siregar, Onan Marakali (Peneliti.net, 2024)
Human resources in the organization have an important role, in that all the potential that exists in human resources can be utilized as an effort to be able to achieve success in achieving goals both individually and in the organization. This success can be seen in the level of employee performance in the organization which is influenced by human capital and talent management. This study aims to analyze how the influence of human capital and talent management on improving employee performance at PT Telkom Witel Medan. This form of research is quantitative research with an associative approach. The population in this study were all employees of PT Telkom Witel Medan data management division totaling 34 people with sampling techniques using saturated sampling. The analysis techniques used are instrument tests, classical assumption tests, multiple linear regression analysis, partial tests, simultaneous tests, and coefficient of determination tests. The results of this study indicate that human capital and talent management variables have a positive and significant effect both partially and simultaneously on employee performance at PT Telkom Witel Medan, and have an effect of 74%, while the remaining 26% is influenced by other factors outside this research model.